NPWP REGISTRATION MECHANISM ON CV. TRIBINA JASAINDO (PRACTICAL WORK AT CV. TRIBINA JASAINDO) - Abdurrakhman Alhakim; Viola Zahra Ananda Kusuma (ConCEPt - Conference on Community Engagement Project, 2022)
The state has various sources of funds, one of which is a tax called Income Tax is a tax from the state, which every year the collection is done directly to the taxpayer. In order to organize all activities in taxation, taxpayers must have a Taxpayer Identification Number (NPWP), as a function for the identity of the taxpayer and to maintain regularity and discipline in payments and conduct supervision in tax administration. The people who want to get NPWP must first make it by qualifying the administrative requirements, which the government has counseled on tax issues. But there are still many who are confused how to register and whether the registration is done manually or electronic systems. Regarding this matter the place of research to carry out practical work is on the CV. Tribina Jasaindo, which is a company engaged in services for document management in Batam City. The company has an address in Ruko Greenland Block I No. 5, Tering Bay, Batam City. At the implementation stage, the author permits to carry out the pratical work on the CV, then submits the design idea according to the title of the practice work, and then the author processes the data information to be carried out the output design.